1986
DOI: 10.2151/jmsj1965.64.6_841
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation of a Convergent Cloud Band over the Japan Sea in Winter; Numerical Experiments

Abstract: The aim of the present paper is to investigate the formation mechanism of a convergent cloud band which appears east of the Korea Peninsula over the western Japan Sea under northwesterly winter monsoon.Numerical experiments with different surface conditions reveal that the land-sea contrast of thermal property between the Peninsula and the Japan Sea plays the leading role in the formation of the convergent cloud band. Less transformation over the cold land causes a mesoscale high pressure in the lower troposph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 21 publications
2
48
1
Order By: Relevance
“…Recently a polar low developed over the Japan Sea was described by and Nic1992, Meteorological Society of Japan nomiya and . In numerical studies, Nagata et al (1986), Nagata (1987), Ikawa et al (1987), and Sasaki and Satomura (1991) simulated snow convective bands over the Japan Sea. The above studies described the synoptic conditions and dynamical structure of mesoscale disturbances in winter monsoon which caused graupel and snow precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a polar low developed over the Japan Sea was described by and Nic1992, Meteorological Society of Japan nomiya and . In numerical studies, Nagata et al (1986), Nagata (1987), Ikawa et al (1987), and Sasaki and Satomura (1991) simulated snow convective bands over the Japan Sea. The above studies described the synoptic conditions and dynamical structure of mesoscale disturbances in winter monsoon which caused graupel and snow precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies showed that cold outbreaks behind a synoptic cyclone respond to the lower boundary conditions to form the JPCZ (Nagata et al 1986;Nagata 1991). This indicates that a synoptic situation in the lower troposphere is also a factor to determine a location of the downstream part of the JPCZ.…”
Section: Discussionmentioning
confidence: 92%
“…Using satellite data, Yagi et al (1986) suggested that the blocking of the mountains north of Korea under a stable stratification forms a convergence on the lee side of the mountains. Nagata et al (1986) and Nagata (1991) studied the formation mechanisms for the JPCZ using the same primitive model as that used in Nagata (1987). They revealed that both of the land-sea thermal contrasts and the blocking effect of the mountains north of Korea contribute to the formation of the JPCZ.…”
Section: Introductionmentioning
confidence: 99%
“…1), the cold air mass crossing the sea becomes modified by the rich heat and moisture fluxes from the warm sea surface below, resulting in instability and convection in the boundary layer (e.g., Ninomiya, 1968;Jhun et al, 1994). Furthermore, if the winds over the sea are relatively strong and persistent, the convection can organize into snowbands, leading to the heavy snowfall on the windward (East Sea facing) side of the Korean Peninsula and the Japan Islands (Nagata et al, 1986;Seo and Jhun, 1991;Lee and Lee, 1994). This often leads to heavy snowfall over short periods of time in the absence of a synoptic scale trough or low system.…”
Section: Introductionmentioning
confidence: 99%